Explorando metodologias teóricas clássicas e quânticas para modelagem e simulação molecular de compostos empregados como agentes de contrastes em MRI - Oliveira, Maria Weruska Pereira de (2020)
Magnetic resonance imaging (MRI) has become one of the most powerful diagnostic methods used in medicine. The impressive growth of this technique is because of the use of substances that are known as contrast agents (CAs). Due to their paramagnetic properties, these substances intensify the contrast of the images obtained by increasing the relaxation rate of water protons in the tissues in which they are distributed and, increasing relaxation. The vast majority of ACs used today are coordination complexes containing the Gd(III) ion, since this ion has a high magnetic moment. This work aimed to carry out the conformational mapping of Gd(III) and Mn(II) complexes with macrocyclic ligands through classical and quantum molecular dynamics and matronymics simulations considering explicit and implicit solvent, to determine their performance in finding its conformational isomers that the literature points out that exist in solution. The molecular systems chosen for this study were derived from the macrocyclic ligands 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (abbreviated by DOTA) and ethylenediamine tetra-acetic acid (EDTA). Based on our results, we could conclude that: (i) because of the high computational cost associated with molecular dynamics with quantum potentials, it was not possible to fully explore the conformational space of these compounds and, therefore, when these strategies were applied, not all conformational isomers were found; (ii) the molecular dynamics using potential derivatives of the QMDFF technique proved to be efficient in the conformational search to a certain extent because despite having low computational cost, it also did not find all the conformational isomers predicted for these systems, finally (iii) we were successful in applying the strategy that featured a combination of short molecular dynamics at randomly obtained temperatures, over a wide range of values, with geometry optimizations using the RM1 semi-empirical method. With this strategy, the four stable conformers for the complex Gd(DOTA)(H2O)-, (A1, IA1, A2, and IA2) were found, through the detailed analysis of geometric data (connection distances, dihedrals, the distance between planes, etc. .,) and energetic (Hfand Gibbs energy). Thus, the most important contribution of this work is to present the community with a simple computational procedure of conformational search for coordination complexes containing macrocyclic ligands, taking explicitly into account the effect of the solvent.